1566 Vibration induced injuries in hands in long-term vibration exposed workers. (24th April 2018) - Gerhardsson, L; Hagberg, M
Abstract : Introduction: Long-term vibration exposure may cause neurophysiological disturbances such as dampness and tingling, reduced grip strength and difficulties in handling small objects. Most of the exposed workers are right-handed and thus, the right hand will usually have a higher vibration exposure than the left hand. In this study we are comparing neurophysiological test results in the right and left hand in long-term vibration exposed workers. The underlying hypothesis is that signs of adverse health effects would be more pronounced in the right hand of the workers. Methods: The study is based on 47 (36 males and 11 females; mean-age 50±12 y; mean exposure time 16 y), all former patients from the department of occupational and environmental medicine, Gothenburg university. The comparison group consisted of 29 randomly selected subjects from the general population of Gothenburg. All participants completed several questionnaires and had a standardised medical examination. Thereafter, neurophysiological tests such as muscle strength tests and the determination of thermal and vibration thresholds were performed. Results: No significant differences were found for temperature and vibration thresholds in dig 2 and 5 bilaterally among the workers. Finger muscle tests (Pinch-grip and 3 Chuck grip) were also of the same magnitude in the right and left hand. Hand grip strength (Jamar), however, was significantly higher in the right hand of the workers. Conclusions: Although differences as regards symptoms and neurophysiological test results in the right and left hand of exposed workers have been reported in several studies, the only significant difference noted in this study was a somewhat higher grip strength in the right hand of the workers. That is to be expected, as most of the participants were right handed and therefore probably stronger in their dominant hand.